PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN PRODUK FASHION PADA ONLINE SHOP YELLOW FACY JEANS MELALUI MEDIA SOSIAL INSTAGRAM - Nadya Imanda; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this research is to know the influence of Service Quality, Trust and Consumer Satisfaction of fashion product at online shop “Yellow Facy Jeans” through social media social instagram. This research was conducted on Yellow Facy Jeans customer in Bekasi Timur in 2017. The method used in this research is non-probability through quota sampling procedure with total sample of 120 respondents. Data collection techniques with questionnaires distributed from a total of 165 subscribes minus 40 customers who did not meet the criteria and the rest 5 customers did not answer the question completely so it could not be tested. The results showed that (1) the F test of Service Quality (X1) and Trust (X2) against Consumer Satisfaction Yellow Facy Jeans (Y) shows that Quality of Service and Trust simultaneously have a significant effect on Consumer Satisfaction in Yellow Facy Jeans; (2) the effect of Service Quality partially on Yellow Facy Jeans Consumer Satisfaction through t test showing sig value of 0,000 < 0,05, which means partial Service Quality significantly influence Consumer Satisfaction on Yellow Facy Jeans ; and (3) the partial influence of Trust on Yellow Facy Jeans Consumer Satisfaction is tested by t test showing sig value of 0,000 <0,5, which means partial Trust has significant effect on Consumer Satisfaction in Yellow Facy Jeans.